Determination of dipping contacts using electrical resistivity tomography - PUTIŠKA, René; DOSTÁL, Ivan; KUŠNIRÁK, David (Contributions to Geophysics and Geodesy, 2012)
Generally, all electrode arrays are able to delineate the contact of two lithostratigraphic units especially with very high resistivity  contrast. However, the image resolution for the location of vertical and dipping structures is different. The responses of dipole-dipole (DD), Wenner alpha (WA), Schlumberger (SCH) and combined pole-dipole (PD) arrays have been computed using the finite difference method. Comparison of the responses indicates that: (1) The dipole-dipole array usually gives the best resolution and is the most detailed method especially for the detection of vertical structures. This array has shown the best resolution to recognize the geometrical characterisation of the fault. (2) The pole-dipole has shown the second best result in our test. The PD is an effective method for detection of vertical structures with a high depth range, but the deepest parts are deformed. (3) Wenner alpha shows a low resolution, inconvenient for detailed investigation of dip structures. (4) The Schlumberger array gives a good and sharp resolution to assess the contact between two lithological units but gives poor result for imaging geometry of dipping contact.